ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUH TINGKAT KONSERVATISME PERUSAHAAN – PERUSAHAAN DI INDONESIA - Muhammad Setio Priambodo; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
The main focus of the financial statements is to provide information regarding earnings. Accounting has a principle called conservatism, namely the precautionary principle in determining the amount of profit. The purpose of this study was to analyze the factors that influence the firm choice of using conservatism principle. Conservatism is the dependent variable in this study as measured by the size of the accrual and market value. The independent variables studied include concentration ratios, corporate risk, company size, capital intensity, and the leverage ratio. Samples are manufacturing companies listed in Indonesia Stock Exchange in 2011-2013. The sample was selected using purposive sampling and obtained a sample of 20 companies. Testing is done by multiple linear regression analysis that has met the test of classical assumptions. The results showed that the capital intensity significantly influence the application of the principle of conservatism. While the size of the company, firm risk, concentration ratio, and leverage does not significantly influence the application of the conservatism principle.